Implementation of Integrity Zones in Educational Institutions: Problems and Readiness for Innovation - Ranu, Meylia Elizabeth; Hermanto, Febrika Yogie; Susilowati, Fitriah Dwi; Fahmi, Moh. Farih; Amirusholihin, Amirusholihin; Ramdhan , Muhammad Rizky (IKIP Widya Darma Surabaya, 2024)
Objective: The integrity zone is an effort to build a work culture that upholds honesty, a strong commitment to upholding justice, and is free from corruption, collusion and nepotism practices. Surabaya State University is one of the institutions that has been entrusted to implement the integrity zone by the Minister of Education of the Republic of Indonesia. The purpose of this study is to analyze the problems in implementing the integrity zone in the faculty and to analyze the level of innovation applied in the faculty. The obstacles and level of innovation faced by the faculty at Surabaya State University are the things that will be studied in this study. Method: This study uses a qualitative method with a multi-case approach. Result: Based on the results of the study, a summary of the problems faced in implementing the integrity zone in the faculty was obtained, namely, first, incomplete socialization. Second, there has been no periodic evaluation. Third, lack of supporting facilities. Fourth, low organizational commitment. Fifth, top leaders have not appeared strongly as role models for implementing the basic principles of enforcing institutional integrity. Novelty: The novelty in this study is to examine the implementation of the integrity zone by analyzing the problems in its implementation that can be used as factors or variables in subsequent studies and to capture the extent to which the institution is ready to carry out bureaucratic reform in public services.